Efektivitas Ekstrak Artemisia vulgaris L. sebagai Hepatoprotektor pada sel-sel Hati Tikus yang Diinduksi Niasin - Laily Rahmawati; Erma Sulistyaningsih; Rosita Dewi (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
The niacin in energy drinks has metabolic product that cause oxidative stress and liver damage, while the liver damage can be prevented by hepatoprotective agents. Scoparone in Artemisia vulgaris L. can act as a hepatoprotector by its antioxidant effect. This study aimed to investigate the effectivity of Artemisia vulgaris L. extract as a hepatoprotector in wistar hepatocytes induced by niacin. This study used 25 male rats which were divided into 5 groups: normal, the negative control, the positive control, the treatment group I, and II. Treatment was conducted for 28 days. The samples were terminated and the hepatocyte were prepared for histological examination. Histological appearance was catagorized as mild, moderate, and severe damage with or without inflamatory cells activity. The data analysis by Kruskal Wallis showed significant difference (p<0,001). Further analysis by Mann Whitney revealed significantly difference (p<0,05) between normal group and all groups, negative control group and positive control group, and positive control group and treatment group I, but not significantly difference between negative control group and treatment group I, negative control group and treatment group II, positive control group and treatment group II, and between treatment groups. The study concluded that the effectivity of Artemisia vulgaris L. extract has not been proven as a hepatoprotector but further study is needed to draw a definite conclusion. Keywords: energy drink, niacin, Artemisia vulgaris L., hepatoprotector